Influencia del programa basado en la Pedagogía de la Ternura en la disminución de la Agresividad en los niños de 4 años en la I.E. Radiantes Capullitos Nº 1564 de la ciudad de Trujillo-2014 - Cueva Otiniano, Mery (2014)
The present study aims to reduce the aggressiveness in children of four years of Educational Institution No. 1564 "Radiantes Capullitos" of the city of Trujillo._x000D_ The research is carried out with a sample of 40 children of 4 years old, is of type applied with quasi-experimental design with experimental group, control group, in pre, and postest._x000D_ The results of the pretest let us know that so many children in the experimental group; as well as the control group, present a high level of aggressive behavior. The postest results after having applied the program based on the pedagogy of tenderness, the children of the experimental group managed to significantly decrease their aggressiveness._x000D_ Key words: Pedagogy of tenderness and aggressive behavior